Characterising the responses of farm mammals to a thoracic squeeze and the relationship to tonic immobility : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Veterinary Science at Massey University, Manawatū, New Zealand - Holdsworth, Sophia Ellen (Massey University, 2023)
Applying compression to the thorax of newborn farm mammals causes immobility accompanied by reduced responsiveness. Traditionally, this response was proposed to arise in neonatal foals due to the ‘thoracic squeeze’ mimicking the compression occurring during birth. Recent findings regarding the responses to the squeeze suggest a link to Tonic Immobility (TI). TI is a temporary and reversible state of reduced responsiveness and immobility with characteristic physiological changes. It is elicited by the collective actions of handling and sustained physical contact with additional pressure (restraint) and may be facilitated by inversion. TI is reported in young and adult animals of numerous species. The aim of this thesis was to examine whether responses to the thoracic squeeze are consistent with TI. First, behavioural responses to a squeeze were explored in lambs, with a focus on determining whether responses persisted beyond the neonatal period. Cortisol responses of healthy neonatal piglets to the squeeze were then investigated to explore similarities in Hypothalamic-Pituitary-Adrenal responses between the squeeze and TI. The final study examined electroencephalographic (EEG) responses of healthy neonatal piglets to a thoracic squeeze under light anaesthesia, to determine whether the squeeze causes changes in brain activity or exerts anti-nociceptive effects such as those reported during TI. The results demonstrated that responses to a thoracic squeeze persist beyond the neonatal period in lambs, and responses are generalised across multiple mammalian species. Furthermore, cortisol responses of piglets to a thoracic squeeze followed a similar pattern to that previously observed during TI in other species. Also consistent with some TI studies, the initial handling and restraint required to apply the squeeze appeared to induce the cortisol response in piglets. No inferences could be made about the effects of a thoracic squeeze on state of awareness in neonatal piglets, or the squeeze’s effect on nociception due to methodological limitations. Nevertheless, the results of this research support the hypothesis that the thoracic squeeze may be classified as a stimulus for inducing TI. Further work is required to characterise the effects of the squeeze on awareness and nociception and to explore the affective experiences of animals subjected to the squeeze.
Keywords: Domestic animals; Nervous system; Effect of stress on; Animal immobilization; Physiological effect; Veterinary physiology; physiology, veterinary science, neonates, farm mammals, thoracic squeeze, tonic immobility, electroencephalogram, cortisol, pigs, sheep; 300902 Veterinary anatomy and physiology